2020
DOI: 10.1007/s13311-019-00807-3
|View full text |Cite
|
Sign up to set email alerts
|

FG-4592 Improves Depressive-Like Behaviors through HIF-1-Mediated Neurogenesis and Synapse Plasticity in Rats

Abstract: Depression, plus the accompanying memory impairment, is one of the leading causes of disability worldwide. Thus, there is a critical need to develop new drugs based on distinct strategies. FG-4592, an inhibitor of prolyl hydroxylase, activates the hypoxia-inducible factor-1 (HIF-1) pathway, to produce multiple effects on cell properties. Here, we examined whether FG-4592 has antidepressant effects, using a chronic unpredictable mild stress (CUMS) procedure to establish rodent depression models. We found that F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Also, our work helps to elucidate the role occupied by another factor: HIF-1α. The present results are consistent with previous studies showed that the upregulation of HIF-1α promoted synapse plasticity by mediating synaptic markers (Li G. et al, 2019 ), and played a beneficial role in post-stroke exercise inducing angiogenesis and neurogenesis (Li C. et al, 2017 ). Recent work demonstrates that exercise could activate the cerebral motor and cognitive circuits by increasing the expression of HIF-1α, suggesting a regulatory role of HIF-1α in exercise-enhanced neuroplasticity (Halliday et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…Also, our work helps to elucidate the role occupied by another factor: HIF-1α. The present results are consistent with previous studies showed that the upregulation of HIF-1α promoted synapse plasticity by mediating synaptic markers (Li G. et al, 2019 ), and played a beneficial role in post-stroke exercise inducing angiogenesis and neurogenesis (Li C. et al, 2017 ). Recent work demonstrates that exercise could activate the cerebral motor and cognitive circuits by increasing the expression of HIF-1α, suggesting a regulatory role of HIF-1α in exercise-enhanced neuroplasticity (Halliday et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the dendritic spine density was observed by Golgi staining. The results revealed significantly decreased densities in the CUMS group, which indicated that stress can decrease synaptic plasticity, and this finding is consistent with previously reported results [ 45 , 46 ]. Notably, EA treatment significantly improved the dendritic spine density.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, the role of estrogen signaling has been highlighted with studies reporting its neuroprotective effects on the brain by sheltering it from inflammation and stress ( Azcoitia et al, 2019 ; Hwang et al, 2021 ), and investigations in animal models of psychiatric disorders and in patients, revealed that this signaling is disturbed and associated with cognitive deficits and also with the manifestations of symptoms that could be reversed with treatments targeting estrogen-signaling pathways ( Hwang et al, 2021 ). To add more Li et al showed that hypoxia-inducible factor-1 (HIF-1) pathway is a promising target for the treatment of depression ( Li et al, 2020 ). Indeed, they reported that HIF-1 may produce beneficial effects on depression, as it targets genes that have been shown to elicit antidepressant effects in animal models (erythropoietin (EPO) and vascular endothelial growth factor (VEGF) genes ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%